Combined transport in Europe: Scenario-based projections of emission saving potentials - Malte Jahn; Paul Schumacher; Jan Wedemeier; André Wolf (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2020)
The paper at hand discusses the different typologies of combined transportation in Europe. It shows that an improvement of handling infrastructure for combined transport can positively reduce environmental costs of trading between regions. However, the expected emission reduction effects are relatively small in comparison to the total emissions of the transport sector. This means that, in order to achieve a substantial reduction of emissions, combined transport initiatives need to be complemented by a reduction of the specific emissions of the relevant transport modes. The paper closes with an outlook towards the development of the combined transportation sector.
Keywords: R4; R40; R48; Q56; 330; combined transport; European Union; hinterland transportation; sustainability; regional economics; Baltic Sea Region